2016
DOI: 10.1016/j.foodcont.2015.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccessibility and changes on cylindrospermopsin concentration in edible mussels with storage and processing time

Abstract: a b s t r a c tThe alkaloid cylindrospermopsin has been recognized of increased concern due to the global expansion of its main producer, Cylindrospermopsis raciborskii. Previous studies have shown that bivalves can accumulate high levels of cylindrospermopsin. Based on the potential for human health risks, a provisional tolerable daily intake of 0.03 mg/kg-body weight has been recommended. However, the human exposure assessment has been based on the cylindrospermopsin concentration in raw food items. Thus, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 47 publications
4
24
1
Order By: Relevance
“…However, broiling treatment for 1 min did not produce any significant reduction in unconjugated CYN in fish muscles, showing a clear influence of the cooking time in this cooking treatment. In this sense, it seems that boiling, steaming and microwaving (0.5–15 min) were not able to alter the availability of CYN in mussels fed CYN-producing Cylindrospermopsis raciborskii [13]. By contrast, and in agreement with our results, CYN concentration decreased in fish muscle (Nile tilapia) injected with the toxin and submitted to steaming and boiling for 1 and 2 min compared to the control group [14].…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…However, broiling treatment for 1 min did not produce any significant reduction in unconjugated CYN in fish muscles, showing a clear influence of the cooking time in this cooking treatment. In this sense, it seems that boiling, steaming and microwaving (0.5–15 min) were not able to alter the availability of CYN in mussels fed CYN-producing Cylindrospermopsis raciborskii [13]. By contrast, and in agreement with our results, CYN concentration decreased in fish muscle (Nile tilapia) injected with the toxin and submitted to steaming and boiling for 1 and 2 min compared to the control group [14].…”
Section: Resultssupporting
confidence: 86%
“…Nevertheless, these data are usually based on raw fish, and fish is not normally consumed raw without processing or cooking. The content of CYN in food may vary due to these procedures [ 13 ], which can indeed generate decomposition products of CYN [ 14 ], modifying the final consumer exposure to the toxin in a quantitative and qualitative way. Thus, it is necessary to achieve a more accurate knowledge on the actual intake of CYN and its degradation products for a correct consumer safety assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Once evaporated to dryness, the residue was resuspended in 1 mL 80% (v/v) MeOH, and the samples were determined. The extraction of CYN from mussels was performed according to Freitas et al (2016) [64], followed by SPE from Guzmán-Guillén et al (2015) [65]. Briefly, lyophilized mussels (1 g) was extracted with 10 mL of 90% (v/v) acetonitrile (ACN) by sonication (15 min) and centrifuged at 4495 g at 4 • C for 15 min.…”
Section: Toxin Analysis In Musselsmentioning
confidence: 99%
“…In addition, another factor of uncertainty in assessing human exposure derives from the fact that it is not clear whether the levels of MC-LR and CYN measured in raw edible matrices correspond to the bioavailable amount. Freitas et al (2014Freitas et al ( , 2016 have shown that factors such as food storage, processing and human digestion can change the MC-LR and CYN bioaccessibility and therefore the risk of human exposure. Thus, a lack of recognition of the likelihood of these hazards is an important factor for the late development of risk management strategies.…”
Section: Balance Of Risks For Agriculture and Public Healthmentioning
confidence: 99%